A preliminary mapping network model for unsafe acts in maritime accidents. Issue 5 (January 2021) - Fu, Shanshan; Zhuang, Hui; Zhang, Changjiang; Xi, Yongtao
Abstract: Unsafe acts are a critical issue causing maritime accidents. In order to explore the correlations between the crew's unsafe acts and the induced maritime accidents, this paper proposes a preliminary mapping network model. Its first part is a hierarchical model, making crews' unsafe acts as the top layer, skill-based failures, rule- and knowledge-based mistakes and violations acts as criteria, and basic unsafe acts (BUA) as the bottom layer. Therein, the BUAs are identified from 413 marine accident/incident investigation reports and 91 crews' questionnaires. The second part is composed of several maritime accident types. The connection links between these two parts are aiming to reveal the correlations between each BUA and the specific maritime accident type. The proposed mapping network model can not only support unsafe acts analysis for one and multiple maritime accidents but also present the common BUAs for safety management.